2022
DOI: 10.1186/s12978-022-01371-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slightly elevated progesterone on hCG trigger day on clinical pregnancy rate in GnRH-ant IVF/ICSI cycles

Abstract: Background It was been agreed that significantly elevated progesterone level on the hCG trigger day have detrimental effect on clinical outcomes in IVF/ICSI cycles. However, few studies explored whether slightly elevated progesterone level also same impact on clinical outcomes. Methods We retrospectively studies the effect of slightly elevated progesterone level on outcomes of IVF/ICSI in GnRH-ant cycles. Propensity score matching was used to confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…4 ). A previous study revealed that CPR with progesterone less than 1.0 ng/mL was significantly higher than progesterone with 1.0 to 1.5 ng/mL [ 20 ], while another study showed significantly lower CPR with less than 0.5 ng/mL [ 18 ]. Meanwhile, progesterone was a dynamic parameter during the process of assisted reproduction, which increasing from the day of oocyte pick-up to the day 3 of embryo culture [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 ). A previous study revealed that CPR with progesterone less than 1.0 ng/mL was significantly higher than progesterone with 1.0 to 1.5 ng/mL [ 20 ], while another study showed significantly lower CPR with less than 0.5 ng/mL [ 18 ]. Meanwhile, progesterone was a dynamic parameter during the process of assisted reproduction, which increasing from the day of oocyte pick-up to the day 3 of embryo culture [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 32 ) set the limit of the hCG daily P level to 1.5 ng/ml, which is widely used in clinical practice. However, studies show that when P>1 ng/ml, the CPR or LBR decreases ( 13 , 19 , 23 ). Only people with normal ovarian response with GnRH antagonist protocols were included for analysis in our study, and P>1 ng/ml affected the LBR of fresh embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…We divided all cycles into 2 groups by the P level on the day of hCG trigger, P<1.0 ng/ml and P≥1.0 ng/ml. This grouping was primarily based on data distribution characteristics and reference to current related research ( 13 , 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations